Photo-curing 3D printing carbon-containing conductive porous material as well as preparation method and application thereof

Through the photocuring 3D printing method of thiol-ene click chemistry and polymerization-induced phase separation, the problems of insufficient polymerization reaction and excessive ink viscosity after the introduction of carbon-containing conductive materials into the photocuring resin are solved, and porous materials with low viscosity and high reaction conversion rate are prepared, which are used in intelligent sensing monitoring, seawater desalination, electromagnetic shielding and other fields.

CN120665428APending Publication Date: 2025-09-19DONGHUA UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510723740.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-31
Publication Date
2025-09-19

AI Technical Summary

Technical Problem

Existing photocurable resins have problems such as insufficient polymerization reaction after introducing carbon-containing conductive materials, excessively high ink viscosity, and weak potential applicability.

Method used

A photocurable 3D printing method using thiol-ene click chemistry and polymerization-induced phase separation is adopted. Thiol-containing oligomers and olefin-containing oligomers are dissolved in a porogen, a conductive carbon-containing material is added, and the thiol-ene click chemistry reaction and polymerization-induced phase separation are carried out using a photoinitiator and the ultraviolet light source of the 3D printer for excitation to generate a porous structure.

Benefits of technology

The printing ink with low viscosity and high reaction conversion rate has been realized, which can be quickly formed to generate conductive porous polymer materials with multi-level pores, expanding its application in multifunctional fields such as intelligent sensing monitoring, seawater desalination, and electromagnetic shielding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120665428A_ABST
    Figure CN120665428A_ABST
Patent Text Reader

Abstract

The invention relates to a photocuring 3D printing carbon-containing conductive porous material as well as a preparation method and application thereof. The method is based on a thiol-ene click chemistry and polymerization induced phase separation principle, a thiol-containing oligomer, an alkenyl-containing oligomer, a conductive carbon material and a pore-foaming agent are compounded into low-viscosity ink, and the multi-scale porous structure is formed in one step by researching polymerization reaction kinetics and rheological properties of the ink and combining a photocuring 3D printing technology. The pore-foaming agent has a solvent function, reduces ink viscosity and induces generation of micro pores, and is combined with macroscopic model design to form a multi-stage pore network. The obtained material shows potential application value in the fields of intelligent sensing, electromagnetic shielding, water treatment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocuring additive manufacturing, and in particular to a photocuring 3D printing carbon-containing conductive porous material and a preparation method thereof. Background Art

[0002] Carbon materials such as various types of carbon nanotubes, graphene, and carbon fibers are often considered to be ideal composite reinforcements due to their unique electrical conductivity and mechanical strength. However, since these materials are mostly black and have high light absorption characteristics (broadband absorption in the ultraviolet-visible light region), the incident light intensity in the internal area of ​​the photocurable solution decays sharply, resulting in incomplete internal curing. The layer-by-layer slicing printing strategy using photocuring 3D printing technology can significantly reduce the optical path for curing each layer by decomposing the three-dimensional structure into two-dimensional thin layers (single layer thickness is usually less than 100 microns), which not only ensures sufficient cross-linking of the composite resin, but also avoids internal defects caused by decreased light intensity. This layered curing mechanism effectively solves the light absorption limitation in composite systems of such carbon-containing conductive materials and lays the foundation for the controllable preparation of complex conductive structures.

[0003] Liu Wendi (CN 119505085 A) used palm oil fatty acid acrylamide ethyl ester as raw material, added a small amount of graphene oxide, and used 3D printing technology to prepare graphene oxide-reinforced palm oil-based ion-conductive elastomers, and demonstrated the sensing and monitoring effect. However, the dense cross-linked network formed by the resin limits the material from further exerting more functions to a certain extent. At the same time, porous polymer materials are often used as multifunctional substrates due to their high porosity and high specific surface area, such as electromagnetic shielding, water adsorption and purification, thermal insulation, and intelligent monitoring. Therefore, if a porous polymer network with conductivity can be prepared by photocuring 3D printing technology, it is possible to further construct a multi-scale, multi-patterned porous material matrix, expanding their potential uses. Summary of the Invention

[0004] The present invention aims to solve the problems of insufficient polymerization reaction after the introduction of carbon-containing conductive materials into existing photocurable resins, excessively high ink viscosity, and weak potential applicability, and further provides a method for preparing photocurable 3D printed carbon-containing conductive porous materials based on thiol-ene click chemistry and polymerization-induced phase separation.

[0005] The present invention provides a photocurable 3D printing carbon-containing conductive porous material. A mercapto group-containing oligomer and an olefinic group-containing oligomer are dissolved in a porogen, a conductive carbon-containing material is added, and under the excitation of a photoinitiator and the ultraviolet light source of a 3D printer, a mercapto group-olefinic group click chemical reaction occurs and polymerization-induced phase separation occurs, thereby generating a porous structure. A 3D model is then used to construct a conductive porous polymer material containing multi-level pores.

[0006] The present invention also provides a method for preparing a carbon-containing conductive porous material by photocuring 3D printing, comprising the following steps:

[0007] Step S1: Preparation of slurry: dissolving a mercapto-containing oligomer and an olefin-containing oligomer in a porogen, adding a conductive carbonaceous material and a photoinitiator, stirring in the dark for 1 hour, and sonicating in the dark for 30 minutes in an ultrasonic machine to obtain a light-curable 3D printing ink;

[0008] Step S2: Ink performance testing: Under the irradiation of a portable laser, the prepared ink is subjected to real-time infrared monitoring to perform reaction kinetics testing, and the conversion rate and conversion rate of characteristic groups before and after the ink reaction are calculated; the rheological properties of the ink are tested using a rheometer to obtain parameters such as viscosity and gel curing time;

[0009] Step S3: 3D printing: using a light-curing 3D printer to print the prepared ink, adjusting the equipment parameters with reference to the parameters in step S2, and obtaining conductive porous materials with various macroscopic configurations by designing a 3D model in advance;

[0010] Step S4: sample cleaning: immersing the sample in a cleaning solvent for cleaning;

[0011] Step S5: Sample drying: Dry the printed structure in a vacuum oven to obtain the final product.

[0012] The present invention also provides an application of photocuring 3D printing of carbon-containing conductive porous materials.

[0013] This paper, based on a photocurable 3D printing strategy using thiol-ene click chemistry and polymerization-induced phase separation, formulates an ink with low viscosity, high reaction conversion rate, and rapid prototyping for photocurable 3D printing by adjusting the types and amounts of raw materials. By adjusting 3D printer parameters to match the printing ink, a conductive porous polymer material with multi-level porosity was designed and prepared.

[0014] Compared with the prior art, the positive effects of this application are:

[0015] 1. In the printing ink preparation process of the present invention, the porogen can also be regarded as a solvent for the oligomer, which reduces the viscosity of the ink to a certain extent, thereby offsetting the increase in ink viscosity caused by the addition of carbon materials, thereby improving the molding accuracy of the printing process;

[0016] 2. From the perspective of porogens, they can simultaneously initiate polymerization-induced phase separation during the process of generating polymers through click chemistry reactions, generating micron-scale porous polymer network structures and expanding the applicability of materials.

[0017] 3. The preparation method of the present invention is simple to operate, avoids the functionalization post-finishing process, reduces the impact on the porous polymer network, can more efficiently customize light-curing 3D printing materials, and the finished product is more stable.

[0018] Overall, this conductive porous material matrix, fabricated in a single step using photopolymerization 3D printing, simplifies the production process compared to research strategies that prioritize printing followed by functionalization, reduces the impact on material structure and performance instability, and improves controllability of material properties. The resulting polymer simultaneously polymerizes within the porogen, inducing phase separation to create microscopic pores. Combined with the macroscopic pores and structures designed in the 3D model, this approach demonstrates potential applications in diverse fields such as intelligent sensing and monitoring, seawater desalination, and electromagnetic shielding. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic diagram of the process for preparing a light-cured 3D printed carbon-containing conductive porous material according to the present invention and the chemical equation for the thiol-ene click reaction involved;

[0020] Figure 2 is the viscosity of all examples at a shear frequency of 1 Hz;

[0021] Figure 3 is the gelation and curing time of all examples under the conditions of 1% shear strain and 5 Hz frequency;

[0022] Figure 4 is a graph of thiol time-conversion rate for all embodiments;

[0023] Figure 5 is a graph showing the alkenyl group time-conversion rate for all examples;

[0024] Figure 6 This is an infrared comparison diagram of Example 1 and the raw material;

[0025] Figure 7 This is a scanning electron microscope image of Example 2 / 3;

[0026] Figure 8 This is a physical diagram of Example 4;

[0027] Figure 9 This is a scanning electron microscope image of Example 5;

[0028] Figure 10 This is a real picture of the evaporation test in Example 6. DETAILED DESCRIPTION

[0029] Below in conjunction with specific embodiment, further set forth the present invention.Should be understood that these embodiments are only used to illustrate the present invention and are not used in limiting the scope of the present invention.In addition, should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall equally within the scope limited by the appended claims of the application.

[0030] A photocurable 3D printed carbon-containing conductive porous material is prepared by dissolving a thiol-containing oligomer and an olefin-containing oligomer in a porogen, adding a conductive carbon-containing material, and exciting the material with a photoinitiator and the ultraviolet light source of the 3D printer to cause a thiol-olefin click chemical reaction and polymerization-induced phase separation, thereby producing a porous structure. A 3D model is then used to construct a conductive porous polymer material containing multi-level pores.

[0031] Preferably, the mercapto group-containing oligomer of the present invention is at least one of pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(2-mercaptoacetate), trimethylolpropane tris(3-mercaptopropionate), and 1,4-butanediol di(3-mercaptopropionate).

[0032] Preferably, the alkenyl-containing oligomer of the present invention is at least one of polyethylene glycol diacrylate, triethylene glycol divinyl ether, trimethylolpropane triacrylate, and epoxy acrylate.

[0033] Preferably, the porogen of the present invention is at least one of anhydrous ethanol, polyethylene glycol 200, and N,N-dimethylformamide.

[0034] Preferably, the conductive carbon material of the present invention is at least one of carbon nanotubes, graphene, and carbon fibers.

[0035] Preferably, the photoinitiator of the present invention is at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.

[0036] A method for preparing a carbon-containing conductive porous material by photocuring 3D printing comprises the following steps:

[0037] Step S1: Preparation of slurry: dissolving mercapto-containing oligomers and olefin-containing oligomers in a porogen, adding a conductive carbonaceous material and a photoinitiator, stirring in the dark for 1 hour, and ultrasonically treating in the dark for 30 minutes in an ultrasonic machine to obtain a light-curable 3D printing ink.

[0038] The dosage of each raw material is as follows: the molar ratio of mercapto-containing oligomer to olefin-containing oligomer is 1:1-4; the dosage of porogen is 70%-400% of the total weight of oligomer; the dosage of conductive carbon-containing material is 0%-5% of the total weight of oligomer; and the dosage of photoinitiator is 0.1%-6% of the total weight of oligomer.

[0039] Step S2: Ink performance test: Under the irradiation of a portable laser, the prepared ink is subjected to real-time infrared monitoring for reaction kinetics testing, and the conversion rate and conversion rate of characteristic groups before and after the ink reaction are calculated; the rheological properties of the ink are tested using a rheometer to obtain parameters such as viscosity and gel curing time.

[0040] Step S3: 3D printing: The prepared ink is printed using a light-curing 3D printer, and the equipment parameters are adjusted according to the parameters in step S2. By designing a 3D model in advance, a conductive porous material with various macroscopic configurations is obtained.

[0041] The initial exposure time of light curing is 30-60s, the curing time of each layer is 2-6s, the light-off delay time is 0-5s, and the layer thickness is 40-100μm.

[0042] Step S4: Sample cleaning: immerse the sample in a cleaning solvent for cleaning.

[0043] The cleaning solvent is anhydrous ethanol or acetone, and the processing time is 1-12 hours.

[0044] Step S5: Sample drying: Dry the printed structure in a vacuum oven to obtain the final product.

[0045] The vacuum degree of the vacuum oven is 1 bar, the drying temperature is 50-70°C, and the drying time is 1-6 hours.

[0046] The specific process of the reaction kinetics test of the present invention is as follows: a portable laser is used to adjust the intensity and wavelength of the printer light source to simulate the light source of a 3D printer. The prepared ink is applied to an infrared monitoring platform and, under laser irradiation, the wavelength range of the laser is 400-4000 cm-1 at 1 second intervals. -1 Scan the sample internally to monitor the thiol groups (approximately 2570 cm -1 ) and olefins (about 1635cm -1 The conversion rate was calculated by the ratio of the peak area before and after the reaction. After normalization, the conversion rates at different time points were subjected to nonlinear fitting, and the coefficient of determination (R 2 ) must be greater than 0.95.

[0047] The specific process for rheological properties testing is as follows: The ink's rheological properties were tested using a rheometer. For viscosity testing, simply set the program to shear rheology, adjust the shear frequency to 0.1 Hz, and output a value every 2 seconds for a total test duration of 100 seconds. The average of the 50 data points outputted was the viscosity value at the fixed shear frequency.

[0048] During the gelation and curing time test, within the shear rheology measurement program range, the shear strain was set to 1%, the shear frequency was set to 5 Hz, and the storage modulus (G') and loss modulus (G") were output every 1 second. At the 20th second of the test, a simulated light source was irradiated on the ink being tested, causing the ink to react and form a gel-like substance. During this process, G' and G" experienced a significant rise followed by a stable fluctuation. The time of the significant rise was recorded as the gelation and curing time.

[0049] An application of photocuring 3D printing of carbon-containing conductive porous materials.

[0050] Specifically, as a water treatment material, it can be used as a water evaporator device to accelerate the evaporation of water, and can be used for seawater desalination, purification of heavy metal wastewater, and removal of ions, pollutants or heavy metals in water.

[0051] As an electromagnetic shielding material, it can protect sensitive individuals from electromagnetic radiation from everyday electronic devices. By adjusting its pore structure, it reduces electromagnetic wave reflection and prevents secondary radiation contamination. It can also be printed into flexible armor that better conforms to the body's curves or embedded in ordinary clothing for concealed protection.

[0052] As a pressure sensor material, when the material is deformed by external forces, the resistance of the internal conductive network changes. Combined with a digital multimeter, it can monitor and record the changes in resistance and strain of the pressure sensor in real time, outputting different signals. Alternatively, combined with signal conditioning modules, data acquisition equipment, main control units, communication modules, and other hardware and embedded software, it can enable real-time monitoring of human motion, physiological signals (such as pulse and respiration), or object deformation using a mobile phone.

[0053] The technical solution of the present invention is described in detail below with reference to the embodiments:

[0054] In the examples of the present invention, pentaerythritol tetrakis(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), polyethylene glycol diacrylate, and triethylene glycol divinyl ether were purchased from Shanghai Yuanye Biotechnology Co., Ltd., 2,4,6-trimethylbenzoyl-diphenylphosphine oxide was purchased from Shanghai Titan Technology Co., Ltd., and anhydrous ethanol and polyethylene glycol 200 were purchased from Sinopharm Chemical Reagent Co., Ltd. Carboxylated multi-arm carbon nanotubes were purchased from Shenzhen Jiasheng New Materials Co., Ltd.

[0055] Example 1

[0056] Prepare 3D printing ink according to step S1. The specific formula of the ink raw materials is:

[0057] (a) the molar ratio of pentaerythritol tetrakis(3-mercaptopropionate) (containing a mercapto oligomer) to polyethylene glycol diacrylate (containing an olefin oligomer) is 1:4;

[0058] (b) the amount of anhydrous ethanol used is 185% of the total mass of the oligomer;

[0059] (c) The amount of carboxylated multi-arm carbon nanotubes is 2% of the total mass of the oligomer;

[0060] (d) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is used in an amount of 2% of the total weight of the oligomer;

[0061] According to step S2, the printing ink prepared in step S1 is subjected to rheological test and reaction kinetics measurement. The specific results are as follows: Figure 2 — Figure 5 shown.

[0062] According to the procedure of step S3, first refer to the relevant parameters obtained in step S2, and set the printing conditions to an initial exposure time of 45s, 5 printing layers, 60μm thickness per layer, 4s curing time per layer, and 3s delayed light-off time. Then print the model into a 16mm hollow cube, where the size of each hollow micropore is 1.5mm, and there are 4×4 interconnected small holes.

[0063] Follow step S4 and wash in anhydrous ethanol for 1 h.

[0064] According to step S5, the mixture was dried in a vacuum oven at a vacuum degree of 1 bar at a drying temperature of 70° C. for 1.5 h.

[0065] Example 2

[0066] Prepare 3D printing ink according to step S1. The specific formula of the ink raw materials is:

[0067] (a) the molar ratio of pentaerythritol tetrakis(3-mercaptopropionate) (containing a mercapto oligomer) to polyethylene glycol diacrylate (containing an olefin oligomer) is 1:4;

[0068] (b) the amount of anhydrous ethanol used is 200% of the total mass of the oligomer;

[0069] (c) The amount of carboxylated multi-arm carbon nanotubes is 5% of the total mass of the oligomer;

[0070] (d) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is used in an amount of 4% of the total weight of the oligomer;

[0071] According to step S2, the printing ink prepared in step S1 is subjected to rheological test and reaction kinetics measurement. The specific results are as follows: Figure 2 — Figure 5 shown.

[0072] According to the procedure in step S3, first refer to the relevant parameters obtained in step S2, and set the printing conditions to an initial exposure time of 55s, 6 printing layers, 50μm thickness per layer, 4.5s curing time per layer, and 4s delay light off time. Then print the model into a 33×21×5mm cubic structure.

[0073] Follow step S4 and wash in anhydrous ethanol for 1 h.

[0074] According to step S5, the mixture was dried in a vacuum oven at a vacuum degree of 1 bar at a drying temperature of 70° C. for 1.5 h.

[0075] Example 3

[0076] Following the steps of Example 2, a mold was formed into a periodic grid structure of a 33 × 21 × 5 mm lattice plate, where each grid measured 3 × 3 × 2.5 mm, for a total of 8 × 5 = 40 grids, and the prism length between adjacent grids was 1 mm. All other conditions, including the formulation and steps, remained unchanged.

[0077] Example 4

[0078] Prepare 3D printing ink according to step S1. The specific formula of the ink raw materials is:

[0079] (a) the molar ratio of trimethylolpropane tris(3-mercaptopropionate) to polyethylene glycol diacrylate (containing an olefinic oligomer) is 1:3;

[0080] (b) the amount of anhydrous ethanol used is 200% of the total mass of the oligomer;

[0081] (c) The amount of carboxylated multi-arm carbon nanotubes is 1.5% of the total mass of the oligomer;

[0082] (d) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is used in an amount of 2% of the total weight of the oligomer;

[0083] According to step S2, the printing ink prepared in step S1 is subjected to rheological test and reaction kinetics measurement. The specific results are as follows: Figure 2 — Figure 5 shown.

[0084] Following the procedure in step S3, referring to the parameters obtained in step S2, the printing conditions were set to an initial exposure time of 45 seconds, five layers with a thickness of 60 μm per layer, a curing time of 4 seconds per layer, and a light-off delay of 2 seconds. The model was then printed, resulting in a 16 mm hollow cube. Each micropore was 1.5 mm in size, with a total of 4 × 4 interconnected holes.

[0085] Follow step S4 and wash in anhydrous ethanol for 1 h.

[0086] According to step S5, the mixture was dried in a vacuum oven at a vacuum degree of 1 bar at a drying temperature of 70° C. for 1.5 h.

[0087] Example 5

[0088] Prepare 3D printing ink according to step S1. The specific formula of the ink raw materials is:

[0089] (a) the molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) ester (containing mercapto oligomer) to triethylene glycol divinyl ether (containing alkenyl oligomer) is 1:1.5;

[0090] (b) the amount of polyethylene glycol used is 60% of the total mass of the oligomer;

[0091] (c) The amount of carboxylated multi-arm carbon nanotubes is 1.5% of the total mass of the oligomer;

[0092] (d) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is used in an amount of 1% of the total weight of the oligomer;

[0093] According to step S2, the printing ink prepared in step S1 is subjected to rheological test and reaction kinetics measurement. The specific results are as follows: Figure 2 — Figure 5 shown.

[0094] According to the procedure of step S3, first refer to the relevant parameters obtained in step S2, and set the printing conditions to an initial exposure time of 40s, 4 printing layers, 100μm thickness per layer, 3.5s curing time per layer, 1s delay light off time, and then print the model into a 16mm hollow cube, where the size of each hollow micropore is 1.5mm, and there are 4×4 interconnected small holes.

[0095] Follow step S4 and select acetone for 12 h.

[0096] According to step S5, the mixture was dried in a vacuum oven at a vacuum degree of 1 bar at a drying temperature of 50° C. for 5 h.

[0097] Example 6

[0098] Prepare 3D printing ink according to step S1. The specific formula of the ink raw materials is:

[0099] (a) the molar ratio of pentaerythritol tetrakis(3-mercaptopropionic acid) ester (containing mercapto oligomer) to triethylene glycol divinyl ether (containing alkenyl oligomer) is 1:1.5;

[0100] (b) the amount of polyethylene glycol used is 80% of the total mass of the oligomer;

[0101] (c) The amount of carboxylated multi-arm carbon nanotubes is 4% of the total mass of the oligomer;

[0102] (d) 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is used in an amount of 4% of the total weight of the oligomer;

[0103] According to step S2, the printing ink prepared in step S1 is subjected to rheological test and reaction kinetics measurement. The specific results are as follows: Figure 2 — Figure 5 shown.

[0104] According to the procedure of step S3, first refer to the relevant parameters obtained in step S2, and set the printing conditions to an initial exposure time of 45s, 5 printing layers, 90μm thickness per layer, 4s curing time per layer, and 2s delay light off time. Then print the model to form a periodic grid structure of a 33×21×5mm grid plate, where each grid is 3×3×2.5mm in size, with a total of 8×5=40 grids, and the prism length between adjacent grids is 1mm.

[0105] Follow step S4 and select acetone for 12 h.

[0106] According to step S5, the mixture was dried in a vacuum oven at a vacuum degree of 1 bar at a drying temperature of 50° C. for 6 h.

[0107] In the present invention, the viscosity of the ink involved in all embodiments is measured at a shear frequency of 1 Hz, and the curing time is measured under the conditions of 1% shear strain and 5 Hz frequency, with a wavelength of 405 nm and an intensity of about 8000 μw / cm 2 The portable laser irradiation is used to record the time when the storage modulus of the ink changes suddenly before and after irradiation. The rheological data of the ink can be seen. Figure 2 and Figure 3 .according to Figure 2 It can be seen that the viscosity of the ink is less than 1 Pa·s except for Example 6, showing low viscosity characteristics, which provides a basic guarantee for the accuracy of 3D printing. Figure 3 It can be seen that the ink can be cured within 5 seconds, showing the characteristics of rapid prototyping.

[0108] In the present invention, all the embodiments involved in the ink reaction dynamics test are that the ink is subjected to a wavelength of 405nm and an intensity of about 8000μw / cm 2 Portable laser irradiation. At 400-4000cm -1 The samples were scanned within a wavenumber range to monitor the changes of the characteristic groups thiol and olefin groups respectively, and the conversion rate was calculated using the ratio of the peak area before and after the reaction. After normalization, nonlinear fitting was performed on the time and conversion rate, and the determination coefficient (R 2 ) are greater than 0.95, and the conversion rate and the time to reach the equilibrium of conversion rate are obtained. The specific values ​​can be seen Figure 4 and Figure 5 The thiol and olefin conversion rates of all examples can reach approximately 60% and 85% or even higher, respectively, which is close to the results of carbon-free photocurable polymers shown in the existing literature (Wanqi Feng. Facile and rapid synthesis of flexible PEG porous polymers as substrates for functional materials by thiol-ene click chemistry, Chemical Engineering Journal, 2023, 470: 144078), demonstrating the adaptability of light sources, conductive carbon materials, initiators, and precursor dosages.

[0109] In the present invention, Figure 1 The thiol-ene click reaction mechanism of the present invention is demonstrated. Example 1 was characterized by infrared spectroscopy to compare with the raw materials before and after the reaction, indicating that the reaction occurred successfully. It can be observed that the characteristic group -SH is at 2569 cm -1 and C=C bond at 1635cm -1 The vibration peaks at α and β were significantly weakened, indicating that the UV-light-induced thiol-ene click reaction did occur.

[0110] In the present invention, scanning electron microscopy was performed on Examples 2 / 3 and 5, as shown in FIG. Figure 7 and Figure 9 It can be observed that their internal structures have microscopic pores caused by phase separation, and the surface is covered with granular substances, indicating that carboxylated carbon nanotubes have been successfully doped into the structure.

[0111] In the present invention, the shielding effectiveness of Examples 2, 3, and 6 was tested using a vector network analyzer and a waveguide. The specific values ​​are shown in Table 1. The maximum shielding effectiveness values ​​of all examples were greater than 20 dB, indicating that the materials can shield over 90% of electromagnetic waves. A comparison of Examples 2 and 3 also shows that, with a change in configuration, the porous polymer material can be transformed into an absorption-based electromagnetic shielding material, reducing secondary radiation, lowering mutual interference between devices, and stabilizing the electromagnetic environment.

[0112] In the present invention, the water evaporation purification performance of Example 2, Example 3, and Example 6 was also tested. The xenon lamp light source was used to simulate solar illumination to absorb, evaporate, and purify seawater. The ion concentration and evaporation rate in the solution before and after purification were tested. The specific values ​​are shown in Table 2. The physical morphology of all samples is shown as follows Figure 10 The evaporation rates of all tested examples were greater than 1.9 kg m -2 h-1 After purification, the ion removal rate reaches more than 99.5%, showing excellent water purification capabilities.

[0113] Table 1 Comparison of electromagnetic shielding parameters

[0114] Example <![CDATA[SE T ]]> <![CDATA[SE R ]]> A Absorption ratio R reflection ratio Example 2 37.979dB 4.960dB 0.323 0.677 Example 3 24.323dB 1.996dB 0.633 0.363 Example 6 21.368dB 1.899dB 0.640 0.352

[0115] Table 2 Comparison of seawater evaporation purification parameters

[0116]

[0117] Table 3 Comparison of sensing parameters

[0118] Example Sensitivity (0-15kPa) Response range Example 1 <![CDATA[-3.55kPa -1 ]]> 0-130kPa Example 4 <![CDATA[-2.86kPa -1 ]]> 0-160kPa Example 5 <![CDATA[-2.43kPa -1 ]]> 0-180kPa

[0119] In the present invention, a digital multimeter is used in conjunction with a universal material testing machine to monitor and record the resistance and strain changes of Example 1, Example 4 and Example 5 in real time. The shapes of all samples are as follows. Figure 8 The actual picture of Example 4 is shown. During the test, the initial resistance (R0) of the pressure sensor and the resistance value (R) under different strain conditions were recorded, and the resistance change rate and sensitivity factor were further calculated based on these data. The specific values ​​are shown in Table 3. The sensitivity of all tested examples can reach -2.4kPa. -1 , and the response range can reach more than 100kPa, showing its applicability in the field of intelligent sensing monitoring.

Claims

1. A photocurable 3D printed carbon-containing conductive porous material, characterized in that: By dissolving thiol-containing oligomers and olefin-containing oligomers in a porogen, and adding conductive carbon-containing materials, thiol-olefin click chemistry reactions and polymerization-induced phase separation occur under the excitation of photoinitiators and ultraviolet light sources of 3D printers, producing a porous structure. A conductive porous polymer material containing multi-level pores is constructed using a 3D model.

2. The light-curing 3D printing carbon-containing conductive porous material according to claim 1, characterized in that: The mercapto-containing oligomer is at least one of tetrakis(3-mercaptopropionic acid) pentaerythritol ester, tetrakis(2-mercaptoacetic acid) pentaerythritol ester, trimethylolpropane tris(3-mercaptopropionate), and 1,4-butanediol di(3-mercaptopropionate).

3. The photocurable 3D printing carbon-containing conductive porous material according to claim 1, characterized in that The alkenyl-containing oligomer is at least one of polyethylene glycol diacrylate, triethylene glycol divinyl ether, trimethylolpropane triacrylate, and epoxy acrylate.

4. The light-curing 3D printing carbon-containing conductive porous material according to claim 1, characterized in that: The porogen is at least one of anhydrous ethanol, polyethylene glycol 200, and N,N-dimethylformamide.

5. The light-curing 3D printing carbon-containing conductive porous material according to claim 1, characterized in that: The conductive carbon material is at least one of carbon nanotubes, graphene, and carbon fibers.

6. The photocurable 3D printing carbon-containing conductive porous material according to claim 1, characterized in that: The photoinitiator is at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide.

7. A method for preparing the 3D printed carbon-containing conductive porous material according to claim 1, characterized in that: The steps include: Step S1: Preparation of slurry: dissolving a mercapto-containing oligomer and an olefin-containing oligomer in a porogen, adding a conductive carbonaceous material and a photoinitiator, stirring in the dark for 1 hour, and sonicating in the dark for 30 minutes in an ultrasonic machine to obtain a light-curable 3D printing ink; Step S2: Ink performance testing: Under the irradiation of a portable laser, the prepared ink is subjected to real-time infrared monitoring to perform reaction kinetics testing, and the conversion rate and conversion rate of characteristic groups before and after the ink reaction are calculated; the rheological properties of the ink are tested using a rheometer to obtain parameters such as viscosity and gel curing time; Step S3: 3D printing: using a light-curing 3D printer to print the prepared ink, adjusting the equipment parameters with reference to the parameters in step S2, and obtaining conductive porous materials with various macroscopic configurations by designing a 3D model in advance; Step S4: Sample cleaning: immersing the sample in a cleaning solvent for cleaning; Step S5: Sample drying: Dry the printed structure in a vacuum oven to obtain the final product.

8. The method for preparing a light-cured 3D printed carbon-containing conductive porous material according to claim 7, characterized in that: The amounts of raw materials used in step S1 are as follows: the molar ratio of the mercapto-containing oligomer to the olefin-containing oligomer is 1:1-4; the amount of the porogen is 70%-400% of the total mass of the oligomer; the amount of the conductive carbon-containing material is 0%-5% of the total mass of the oligomer; and the amount of the photoinitiator is 0.1%-6% of the total mass of the oligomer.

9. The method for preparing a light-cured 3D printed carbon-containing conductive porous material according to claim 7, characterized in that: In step S3, the initial exposure time for light curing is 30-60s, the curing time for each layer is 2-6s, the light-off delay time is 0-5s, and the layer thickness is 40-100μm; the cleaning solvent in step S4 is anhydrous ethanol or acetone, and the processing time is 1-12h; in step S5, the vacuum degree of the vacuum oven is 1 bar, the drying temperature is 50-70℃, and the time is 1-6h.

10. An application of a light-cured 3D printing carbon-containing conductive porous material prepared by the preparation method according to claim 7.

Citation Information

Patent Citations

  • Preparation method of palm oil-based ionic conductive elastomer

    CN119505085A